Lacanian psychotherapy : theory and practical applications - Miller, Michael J. (Michael Joseph), 1976- (New York : Routledge/Taylor & Francis Group, 2011)
'The work of Jacques Lacan is associated more with literature and philosophy than mainstream American psychology, due in large part to the dense language he often employs in articulating his theory - often at the expense of clinical illustration. As a result, his contributions are frequently fascinating, but their utility in the therapeutic setting can be difficult to pinpoint. Lacanian Psychotherapy aims to fill in this clinical gap by presenting theoretical discussions in clear, accessible language and applying them to several chapter-length case studies, thereby demonstrating their clinical relevance. The central concern of this book is the application of Lacan's notion that the unconscious is structured like, and by, language. This implies a peculiar manner of listening ('to the letter') and intervention, which Miller applies to a number of common clinical concerns - including case formulation, dreams, transference, and diagnosis - in the context of psychotherapy'--Provided by publisher.
Keywords: Psychoanalytic Theory; Psychoanalytic Therapy -- methods